KHASYĀ AS MEDIATOR IN EQUITABLE AND DRIVE FOR WATER GOVERNANCE MODELS IN RURAL COMMUNITIES - andi alfira; Syaparuddin Razak; Jumarni (Universitas Muhammadiyah Surabaya, 2026)
This study examines the role of khasyā as a mediating mechanism linking Islamic ethical values to the intention to support equitable and sustainable water governance in rural Muslim communities. Grounded in Islamic Environmental Ethics Theory and Islamic Leadership Theory, the study investigates the relationships among simplicity, environmental awareness, justice-oriented leadership, khasyā, and the Drive for Water Governance. A quantitative cross-sectional survey was conducted among 151 rural Muslim residents in South Sulawesi, Indonesia, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that khasyā has a strong positive effect on the Drive for Water Governance (β = 0.812, p < 0.001). Environmental awareness (β = 0.342, p < 0.001) and justice-oriented leadership (β = 0.537, p < 0.001) significantly strengthen khasyā, with justice-oriented leadership demonstrating the greater contribution. Simplicity significantly influences environmental awareness (β = 0.706, p < 0.001) and justice-oriented leadership (β = 0.707, p < 0.001), but its effect on khasyā is fully mediated through these two constructs. Indirect effect analysis further confirms that khasyā significantly mediates the relationships between environmental awareness and water governance (β = 0.277, p < 0.001) as well as justice-oriented leadership and water governance (β = 0.436, p < 0.001). These findings demonstrate that spiritual consciousness serves as a critical pathway through which Islamic ethical values are translated into governance-related behavioral intentions, highlighting the importance of integrating spiritual, ethical, and leadership dimensions into sustainable water governance frameworks